(untitled) (Journal of Education and Development, 2022)
Chinese language teaching is booming and the Chinese language is gradually going global, and more and more Chinese expatriates are paying more attention to the education of their children’s "roots". This paper draws on the teaching theory of the "cultural triangle" to design an online Chinese cultural education resource that is both contemporary and historical, in order to strengthen Chinese children’s sense of national identity and cultural pride.